MANAGEMENT OF THE SLAG AJUSTMENT IN ARC FURNACES - S. V. Korneev; I. A. Trusova (Литьë и металлургия, 2018)
The slag adjustment during steel smelting in arc steelmaking furnaces, the conditions for sponging and the gas load at different amounts of supplied oxygen and the various contents of carbon in the melt were considered. The amount of blown carbon-containing materials in the steelmaking bath is determined.